HUMANISTIC POTENTIAL OF THE AXIOLOGICAL APPROACH IN THE PROCESS OF FOREIGN LANGUAGE TEACHING - Oksana V. Geynа; Natalia А. Kovalska (Alfred Nobel University Publisher, 2021)
The article is devoted to the analysis of the humanistic potential of the axiological approach in foreign language teaching in order to provide conditions for the development and growth of a personality which are considered to be universal human values. It has been established that one of the features of personality's competitiveness, his/her adaptation to the modern socio-cultural and professional environment is high social stability. It has been substantiated that the purpose of professional education should be the upbringing of socially stable specialists who are able to quickly adapt to the changing trends of modern life, as well as able to constantly improve, search the ways to implement professional knowledge, abilities, skills while defending their opinions and maintaining personal positions. Social stability has been considered as one of the features of the personality's competitiveness as well as his/her adaptation to the modern socio-cultural and professional environment. One of the basic methodological approaches to the process of developing the social stability of the personality is the axiological approach. The psychological attitudes and communicative-speech strategies of interaction of individuals in terms of the axiological teaching approach have been determined. It has been noted that today the issue of selecting forms and methods of teaching that would ensure the development of critical thinking of students - future specialists remains important and unsolved. In this regard, the speech event has been analyzed as a humanistic potential that is revealed in foreign language classes. The description of the lesson as a moment of life where the idea of humanization is revealing through the dialogical being of a person who has intentions as well as performs actions specific for a partnership as a psychological phenomenon has been given. The technology of psychocorrection as a condition for the development and growth of a personality has been proposed. It has been proved that providing conditions for the development and growth of a personality during the lesson requires from the teacher not only professional knowledge related to the teaching of a particular discipline, but also psychological literacy and personal maturity. These are factors which can prevent manipulation of another person, i.e. direct imposition of some position on him/her, which is incompatible with the concept of humanization. The promising research directions, which mean the defining the essence and structure of the axiological approach in pedagogy, highlighting new aspects of the teaching paradigm and tools that reflect the essence of the humanistic concept of education have been determined. Today, an important and not fully resolved issue is the selection of forms and methods of teaching that ensure the formation of a stable system of value orientations, which in the future will determine the life and professional path of a university graduate